Implementation of the Learning Cycle 9E with Real-Virtual Practicum to Improve Students' Critical Thinking Skills - Febriani, Gani; Sari, Ika Mustika; Suyana, Iyon (Berkala Ilmiah Pendidikan Fisika, 2025)
Rapid advancements in science and technology have made critical thinking skills increasingly essential. 21st-century education focuses not only on knowledge transfer but also on developing crucial skills to meet future challenges. This study examines the enhancement of students' critical thinking skills by implementing the Learning cycle of the 9E model, which integrates real and virtual practicums on dynamic fluid materials. The research used a pre-experimental design with a pretest-posttest approach involving 27 grade XI students selected via purposive sampling. Data were collected using a critical thinking skills test with 19 two-level multiple-choice questions and analyzed with Rasch modeling techniques. Results showed that the Learning cycle of the 9E model, combining real and virtual practicums, improved students' critical thinking skills by 5.74 logits, indicating a medium level of improvement. The racking technique revealed that initially, difficult questions became easier post-intervention, highlighting a positive impact on learning. Thus, the Learning cycle of the 9E model with real-virtual practicums effectively enhances students' critical thinking skills in dynamic fluid materials. These findings have significant theoretical and practical implications, supporting classroom learning and educational policies. The stacking and racking techniques provide deeper and more accurate analysis results.